2016
DOI: 10.1007/s00204-016-1803-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in the transport of mercuric ions in target tissues

Abstract: Mercury exists in the environment in various forms, all of which pose a risk to human health. Despite guidelines regulating the industrial release of mercury into the environment, humans continue to be exposed regularly to various forms of this metal via inhalation or ingestion. Following exposure, mercuric ions are taken up by and accumulate in numerous organs, including brain, intestine, kidney, liver, and placenta. In order to understand the toxicological effects of exposure to mercury, a thorough understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(94 citation statements)
references
References 222 publications
2
84
0
Order By: Relevance
“…The locus ceruleus is close to the fourth ventricle and so could be exposed to toxins in the cerebrospinal fluid [ 2 ], but we found that locus ceruleus neurons close to the fourth ventricle did contain more inorganic mercury than those at a greater distance from the ventricle. Mercury could also employ a noradrenaline-associated transporter to enter locus ceruleus neurons, in a similar way the renal tubule mercury transporter operates [ 51 ]. Toxic metals could also enter locus ceruleus neurons via retrograde uptake from the extensive axonal connections these neurons have with brain microvessels [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The locus ceruleus is close to the fourth ventricle and so could be exposed to toxins in the cerebrospinal fluid [ 2 ], but we found that locus ceruleus neurons close to the fourth ventricle did contain more inorganic mercury than those at a greater distance from the ventricle. Mercury could also employ a noradrenaline-associated transporter to enter locus ceruleus neurons, in a similar way the renal tubule mercury transporter operates [ 51 ]. Toxic metals could also enter locus ceruleus neurons via retrograde uptake from the extensive axonal connections these neurons have with brain microvessels [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The experimental model of intragastric gavage, used in this work, illustrates the MeHg intake by food consumption. MeHg is formed by a methyl group attached to the Hg atom (CH 3 Hg), and this allows a greater affinity with thiol groups, mainly of protein components [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mercury (Hg) is recognized as a major pollutant and a hazardous metal for living organisms, owing to its toxicity, persistence, and bioaccumulation through the food web [1]. Hg is present under various chemical forms, which have different toxicities and health repercussions [2]. Hg compounds have long been recognized to target the central nervous system in vertebrates, particularly in developing or juvenile animals [3,4].…”
Section: Introductionmentioning
confidence: 99%